Comparable Efficacy of Azithromycin versus Ceftriaxone in Eradicating H. influenzae of Pediatric Nasal Carriers in Iraq (Journal of Basic and Applied Research in Biomedicine, 2022)
Background: Haemophilus influenzae is a major cause of many serious infections. Nasal carriage contributes to upper respiratory tract infections. Its incidence in pediatric people is well detected worldwide. The guidelines for treatment include many classes of antimicrobial agents with graded response according to many factors. Patients and Methods: This study was carried out on 200 pediatric patients with an age range of 1-5 years, divided equally into 2 groups. Nasal swab was taken from both groups prior to medication, looking for H. influenzae. Nasal carriers in each group were defined. Then, the 1st group carriers were then subjected to treatment with ceftriaxone parenterally for 5 days in a dose of 50 mg/kg/d, while the carriers in the 2nd one were treated with azithromycin 200 mg/d orally for 5 days. After the treatment course, 2 days were left, and then another nasal swab was taken from each carrier child. Results: The swabs taken from both groups reveled the ability of both treatment regimens to eradicate H. influenza, with slightly better effect for azithromycin. Conclusion: The results obtained in this study clearly demonstrated the beneficial effect of using a 3rd generation cephalosporin or azithromycin in the eradication of H. influenzae and confirmed the role of antimicrobial agents in targeting the expected upper respiratory tract infections accompanying H. influenzae nasal carriage.